2009
DOI: 10.5539/ass.v5n2p54
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Perception of Effectiveness: Enlightening Malaysian Managers

Abstract: In the past, the leadership style of Malaysian managers has been different from our Western counterparts due to strong cultural differences. However, with the advent of knowledge economy and the transformation of workforce, leadership style of Malaysian managers is said to be altered. This research explored the current state of leadership style among Malaysian managers and its effect on the perception of effectiveness. A survey method was employed and the data was drawn from subordinates who were working in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
4
15
0
2
Order By: Relevance
“…The findings in the research may be in harmony with that of Jayasingam (2009) for it says that the gender of a manager is not a determinant with his/her managem ent style. However, in the study of it was cited that the male managers were the ones who mostly possess the laissez-faire management style.…”
Section: A Management Style Of Women Managerssupporting
confidence: 50%
See 1 more Smart Citation
“…The findings in the research may be in harmony with that of Jayasingam (2009) for it says that the gender of a manager is not a determinant with his/her managem ent style. However, in the study of it was cited that the male managers were the ones who mostly possess the laissez-faire management style.…”
Section: A Management Style Of Women Managerssupporting
confidence: 50%
“…According to Jayasingam (2009) no gender differences were noticed for autocratic leaders. Generally, as autocratic leadership is deemed ineffective on the whole, it is possible that this style is no longer associated with effectiveness regardless of whether a man or woman manager utilizes it.…”
Section: A Management Style Of Women Managersmentioning
confidence: 99%
“…Furthermore, the researchers found that autocratic leadership has a negative significant impact on employee performance supporting the findings of Jayasingam and Cheng (2009). Where it was found that in Autocratic style of leadership, the leaders dominates all actions and decisions and restricts the innovativeness and creativity of employees.…”
Section: Introductionmentioning
confidence: 51%
“…Влияние особенностей национальной и корпоративной культуры на стимулирование инновационного поведения Стимулирование инновационного поведения работников занимает все более важное место в реализации стратегий развития, достижении конкурентных преимуществ и формировании тактических решений предприятий и организаций по всему миру. Особенно этот аспект актуален для тех стран и рынков, которые избирают инновационный путь развития, предполагающий интенсивное использование корпоративных знаний и интеллектуального потенциала, таких, например, как Китай [23], Малайзия [14] и другие активно развивающиеся страны. Российское руководство также заявляет о национальной ориентации на инновационный путь развития, что включает наши компании в круг тех, для кого стимулирование инновационного поведения сотрудников выходит на первый план в обеспечении своей конкурентоспособности.…”
Section: Introductionunclassified